Pengaruh Customer Satisfaction dan Customer Loyalty terhadap Repurchase Intention - Reza Fachmi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The automotive industry is one of the strategic sectors that significantly contributes to Indonesia’s economic growth through job creation and increased national income. Along with the post-COVID-19 economic recovery and the intensifying competition among automotive brands—particularly from Japan, South Korea, and China—companies are required not only to offer quality products but also to deliver a comprehensive customer experience. This study aims to analyze the influence of Customer Satisfaction and Customer Loyalty on Repurchase Intention in the automotive sector. Based on previous literature, there is a strong relationship between satisfaction and loyalty in driving consumers’ intention to repurchase from the same brand. The findings of this study are expected to provide strategic implications for automotive company management in designing customer experience–oriented marketing strategies to improve long-term customer retention.